2011
DOI: 10.1007/s10457-011-9383-6
|View full text |Cite
|
Sign up to set email alerts
|

Forage production in natural and afforested grasslands of the Pampas: ecological complementarity and management opportunities

Abstract: In managed rangelands periods of low primary productivity determine troughs of forage availability, constraining animal production yearround. Although alternative tools to increase forage availability during critical seasons exists, most of them are unaffordable and short-lived in marginal areas. We explore the potential benefits of deciduous tree plantations favoring winter forage productivity by comparing aboveground net primary productivity (ANPP) patterns in herbaceous understory to tree plantations and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
(35 reference statements)
1
4
0
Order By: Relevance
“…Trees reduce irradiance and temperature in summer which likely favors C3 over C4 plants, since C3 grasses have a lower light saturation point and higher efficiency in colder temperatures (Brown 1982, Gardner et al 2003, whereas the growth rate of C4 grasses decreases under shade (Pearcy andEhleringer 1984, Kephart et al 1992). Higher C3 abundance under trees has been reported in other mixed tree-grass systems, for example in North America Archer 1997, Sharrow et al 1999), South America (Del Pilar Clavijo et al 2005, Nordenstahl et al 2011 and South Africa (Cowling 1983). Our findings are consistent with reports of facilitation of C3 grass species as a result of abiotic stress amelioration by shrubs in eastern Uruguay (Fernández et al 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Trees reduce irradiance and temperature in summer which likely favors C3 over C4 plants, since C3 grasses have a lower light saturation point and higher efficiency in colder temperatures (Brown 1982, Gardner et al 2003, whereas the growth rate of C4 grasses decreases under shade (Pearcy andEhleringer 1984, Kephart et al 1992). Higher C3 abundance under trees has been reported in other mixed tree-grass systems, for example in North America Archer 1997, Sharrow et al 1999), South America (Del Pilar Clavijo et al 2005, Nordenstahl et al 2011 and South Africa (Cowling 1983). Our findings are consistent with reports of facilitation of C3 grass species as a result of abiotic stress amelioration by shrubs in eastern Uruguay (Fernández et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…I found that isolated trees in subtropical rangelands can facilitate the growth and increase the nitrogen content of herbaceous biomass, and increase the abundance of C3 winter species within the herbaceous layer. This latter effect can contribute to an improved forage quality along the year, particularly in the winter season, when grass productivity reaches its annual low (Ode et al 1980, Nordenstahl et al 2011. Therefore, a potential expansion of trees into rangelands can have positive effects for livestock productivity, provided that tree cover is kept below the point where light limitation reduces grass growth.…”
Section: Subtropical Grasslands Of South America: Old-growth and Anthmentioning
confidence: 99%
“…Trees reduce irradiance and temperature in summer which likely favors C3 over C4 plants, since C3 grasses have a lower light saturation point and higher efficiency in colder temperatures (Brown, 1982;Gardner et al, 2003), whereas the growth rate of C4 grasses decreases under shade (Pearcy and Ehleringer, 1984;Kephart et al, 1992). Higher C3 abundance under trees has been reported in other mixed tree-grass systems, for example in North America (Scholes and Archer, 1997;Sharrow et al, 1999), South America (Clavijo et al, 2005;Nordenstahl et al, 2011) and South Africa (Cowling, 1983). Our findings are consistent with reports of facilitation of C3 grass species as a result of abiotic stress amelioration by shrubs in eastern Uruguay (Fernández et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…Low production and low quality of pastures are key constraints of livestock productivity on natural grasslands of Uruguay during the colder seasons (Berretta, 2001). In fact, winter is the critical season for livestock productivity since winter forage production usually determines maximum cattle loads (Nordenstahl et al, 2011). The increase of C3 grasses and the overall higher N content of the herbaceous plants growing in the understory of trees can therefore improve the provisioning of forage during the most limiting season.…”
Section: Discussionmentioning
confidence: 99%
“…They did not mention that P. caldenia facilitated this process; however, their statistical analysis showed a strong association between P. caldenia and these two grass species. C 3 afforestation projects in C 4 grasslands of Argentina have documented increases in C 3 grasses beneath planted poplar trees (Nordenstahl, Gundel, Clavijo, & Jobbagy, 2011).…”
Section: Woody Plant Facilitation Of C 3 Grassesmentioning
confidence: 99%